Nutritional status of iodine in pregnancy and its influence on the health of the binomium (Revista Contexto & Saúde, 2020)
Pregnancy is associated with a decline in iodine in the maternal body, which can lead to hypothyroidism in iodine deficient areas, so an adequate intake during pregnancy is critical. Insufficient maternal iodine intake negatively affects the health of the fetus and newborn, with consequences that will last a lifetime. This review aimed to describe the importance of iodine for the gestational period and the effects related to its deficiency in the mother-child binomial. Iodine is known to be essential for fetal brain development in stages such as neurogenesis, neuronal and glial cell differentiation, myelination, migration and synaptogenesis. In this sense, iodine deficiency during pregnancy and extrauterine life can lead to a set of abnormalities called iodine deficiency disorders, which include a spectrum of different diseases, such as hypothyroidism, stillbirth, goiter, congenital anomalies, impaired infant growth and development; delayed psychomotor development; reduced cognitive ability; in addition to increasing fetal and infant mortality rates and being considered the leading preventable causes of childhood mental disability and cretinism. Future studies on the role of iodine deficiency in maternal and fetal health are still needed to clarify how iodine impacts gestational and perinatal outcomes and the possibilities for intervention to prevent or minimize the undesirable effects of iodine deficiency.